2019
DOI: 10.1186/s13053-019-0127-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival by colon cancer stage and screening interval in Lynch syndrome: a prospective Lynch syndrome database report

Abstract: Background We previously reported that in pathogenic mismatch repair (path_MMR) variant carriers, the incidence of colorectal cancer (CRC) was not reduced when colonoscopy was undertaken more frequently than once every 3 years, and that CRC stage and interval since last colonoscopy were not correlated. Methods The Prospective Lynch Syndrome Database (PLSD) that records outcomes of surveillance was examined to determine survival after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 13 publications
5
29
0
Order By: Relevance
“…In addition to the four descriptive reports described above, three hypothesis-testing papers have been published: CRC incidence related to the interval between colonoscopies [16], clinic-pathological stage of colon cancer related to time since last colonoscopy [17] and survival after colon cancer related to time since last colonoscopy [18].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the four descriptive reports described above, three hypothesis-testing papers have been published: CRC incidence related to the interval between colonoscopies [16], clinic-pathological stage of colon cancer related to time since last colonoscopy [17] and survival after colon cancer related to time since last colonoscopy [18].…”
Section: Methodsmentioning
confidence: 99%
“…While 312 of the 425 carriers (73.4%) had a single cancer, 113 (26.6%) had more than one CRC (42 (9.9%) synchronous CRC and 71 (16.7%) metachronous CRC). The mean lapse between the first and the second CRC was 10.5 years (range [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. No differences regarding metachronous and synchronous CRC were evident between MLH1 and MSH2 carriers (p > 0.…”
Section: Resultsmentioning
confidence: 89%
“…ES extended surgery,2 SS segmental surgery,3 mCRC metachronous colorectal cancer,4 Ams families which meet Amsterdam criteria,5 LS Lynch syndrome patients,6 n.r. not reported,7 extended right hemicolectomy is included in extended surgery,8 only considered when initial tumor is right-sided tumor,9 15 years overall survival,10 25 years overall survival.Cancers 2020, 12, 3419…”
mentioning
confidence: 99%
“…Although LS and FCCTX are different entities, they share analogous pedigree features, as found in the current study. The surveillance guidelines for LS are well established ( 31 33 ) and are aimed at the diagnosis of colorectal adenomas, early CRC, and other LS-related cancers. Recent clinical guidelines suggest colonoscopy at least once every 2 years, beginning between age 20 and 25 years ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical guidelines suggest colonoscopy at least once every 2 years, beginning between age 20 and 25 years ( 32 ). The Prospective LS Database reported that colonoscopy performed in intervals of <3 years is beneficial for the follow-up of MMR variant carriers ( 33 , 34 ). Primary prevention screening colonoscopy in asymptomatic family members significantly decreased the risk of CRC in FCCTX ( 35 ).…”
Section: Discussionmentioning
confidence: 99%